Transforming the Islamic Education Curriculum for the Society 5.0 Era: Integrating Technology, Ethics, and Pedagogy - Windy Dian Sari (STAI Hubbulwathan Duri, 2025)
The rise of Society 5.0—a human-centered paradigm that merges advanced technology with solutions to social challenges—necessitates a rethinking of the Islamic education curriculum. Traditional pedagogies alone are insufficient to equip learners with the competencies needed in a digitally driven world, particularly in balancing technological fluency with spiritual and ethical grounding. This qualitative study explores how Islamic educational institutions are adapting their curricula to meet the demands of Society 5.0. Data were collected through purposive sampling involving three institutions in Indonesia. The research employed document analysis and semi-structured interviews with 15 participants, including educators, curriculum developers, and policymakers. Thematic analysis was used to identify key trends in curriculum transformation. The study identified three major areas of curricular change: (1) integration of digital tools to facilitate blended and technology-enhanced learning; (2) incorporation of ethics-focused modules that address the moral use of technology through Islamic frameworks; and (3) adoption of interdisciplinary, inquiry-based approaches that foster critical thinking and real-world application of knowledge. These findings demonstrate a growing capacity within Islamic education to align with the technological and ethical demands of Society 5.0 while preserving core religious values. The study concludes by recommending strategic policy and institutional frameworks to support sustainable curriculum transformation. This model of integration offers valuable insights for Islamic education systems globally seeking to remain relevant in an increasingly digital era.